Flexible sodium-sulfur battery and preparation method thereof
By using NiCoMoS@CC nanoarray structure and NiCoMoLDHs@CC-Na composite anode material in room temperature sodium-sulfur batteries, combined with carbon cloth as the host material, the problems of sodium polysulfide shuttle effect and poor cycle life of room temperature sodium-sulfur batteries were solved, and better reversibility and more stable cycle performance were achieved.
Patent Information
- Application Number
- CN202510149003.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-02-11
AI Technical Summary
Room temperature sodium-sulfur batteries face problems such as sodium polysulfide shuttle effect, poor cycle life and sodium dendrites growth, which seriously hinder their commercial application.
NiCoMoS@CC nanoarray structure is used as the positive electrode material, and NiCoMoLDHs@CC-Na composite anode material is prepared through hydrothermal reaction and vulcanization treatment, and combined with carbon cloth as the host material to realize a flexible sodium-sulfur battery without adhesive structure.
Significantly suppress the shuttle effect, improve electrochemical performance, enhance the stability and conductivity of the electrode material, extend the cycle life, and improve capacity retention.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium-sulfur batteries, and in particular relates to a flexible sodium-sulfur battery and a preparation method thereof. Background Art
[0002] Sodium-sulfur batteries can be divided into three types: high-temperature, medium-temperature and room-temperature sodium-sulfur batteries. Compared with traditional sodium-sulfur batteries (operating temperature 300~350℃), room-temperature sodium-sulfur batteries have high energy density (1274Wh·kg -1 ), low cost, and other significant advantages. However, the current room-temperature sodium-sulfur batteries still face a series of problems, such as the sodium polysulfide shuttle effect, poor cycle life, and sodium dendrite growth, which seriously hinder the commercial application of room-temperature sodium-sulfur batteries. Therefore, the development of positive and negative electrode materials with high cycle stability has become the key to improving the performance of room-temperature sodium-sulfur batteries. Carbon cloth (CC) is considered to be an ideal host material due to its excellent electronic conductivity and mechanical strength. In addition, carbon cloth can also realize an S positive electrode with a binder-free structure to further improve the cycle stability of sodium-sulfur batteries. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a flexible sodium-sulfur battery, which has better reversibility and more stable cycle performance, and can still maintain a high capacity retention rate during long-term cyclic use. The present invention also provides a preparation method thereof.
[0004] The method for preparing the flexible sodium-sulfur battery of the present invention comprises the following steps:
[0005] (1) ultrasonically cleaning the conductive carbon cloth using hydrochloric acid, acetone, anhydrous ethanol and deionized water in sequence to remove pollutants such as organic matter and oxide layer on the surface, placing the cleaned conductive carbon cloth in an oven to dry, and heating the cleaned and dried conductive carbon cloth in a muffle furnace for activation treatment;
[0006] (2) Preparation of NiCoMoS@CC positive electrode: Ni(NO3)2·6H2O, Co(NO3)2·6H2O, Na2MoO4, urea and NH4F were dissolved in deionized water, magnetically stirred until uniformly dissolved, and then vacuum and ultrasonically treated to obtain a mixed solution. The activated conductive carbon cloth was immersed in the mixed solution, heated in a sealed polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction, and then naturally cooled to room temperature to obtain a carbon cloth electrode loaded with a precursor. The carbon cloth electrode loaded with a precursor was ultrasonically cleaned with deionized water and dried in an oven to obtain a NiCoMoLDHs@CC skeleton. The NiCoMoLDHs@CC skeleton was placed in a polytetrafluoroethylene-lined stainless steel autoclave in a Na2S·9H2O aqueous solution and heated for hydrothermal vulcanization, then washed with deionized water and ethanol, and dried in a vacuum oven;
[0007] (3) Preparation of NiCoMoLDHs@CC-Na composite anode: The NiCoMoLDHs@CC skeleton was brought into contact with heated molten metallic sodium in a drying room, and the NiCoMoLDHs@CC-Na composite anode was obtained by spontaneous adsorption of molten sodium.
[0008] Preferably, in step (1), the cleaned and dried conductive carbon cloth is activated by heating it in a muffle furnace in an argon atmosphere at 400-700° C. for 4-8 hours.
[0009] Preferably, in step (2), in the mixed solution, the concentrations of Ni(NO3)2·6H2O, Co(NO3)2·6H2O and Na2MoO4 are all 0.01-0.02M.
[0010] Preferably, in step (2), in the mixed solution, the mass volume concentration of urea is 3-6 g / L, the mass volume concentration of NH4F is 0.8-1.5 g / L, and the vacuum and ultrasonic treatment time is 30-60 min.
[0011] Preferably, in step (2), the hydrothermal reaction is carried out at 140-180° C. for 4-10 hours.
[0012] Preferably, in the hydrothermal vulcanization of step (2), the concentration of Na2S·9H2O in the Na2S·9H2O aqueous solution is 0.1-0.2M, the hydrothermal vulcanization temperature is 120-130°C, and the hydrothermal vulcanization time is 8-12h.
[0013] The present invention also provides a flexible sodium-sulfur battery prepared by the above preparation method.
[0014] Compared with the prior art, the present invention has the following beneficial effects:
[0015] 1. The NiCoMoS@CC nanoarray structure has a polar surface, which can strongly interact with polysulfides, improve electrochemical performance, and has good ability to adsorb and catalyze polysulfides. It can significantly inhibit the shuttle effect, reduce the loss of sulfur active substances, and improve the utilization rate of sulfur, so that the sodium-sulfur battery has better reversibility and more stable cycle performance;
[0016] 2. Loading NiCoMoS onto carbon cloth can enhance the stability of electrode materials, especially in the face of long-term cycle use, it can still maintain a high capacity retention rate;
[0017] 3. The conductivity of carbon cloth itself is good, and after loading transition metal sulfide, the conductivity of electrode materials can be further improved, which helps to improve the overall performance of sodium-sulfur batteries;
[0018] 4. Carbon cloth as a base material has a relatively mature preparation process and low cost. Composite with transition metal sulfides can simplify the manufacturing process and reduce the overall manufacturing cost;
[0019] 5. The application of NiCoMoLDHs@CC skeleton nanoarray structure in the negative electrode of sodium-sulfur batteries provides a large number of surface active sites, which can promote the uniform nucleation and deposition of sodium ions, thereby reducing the local current density in the negative electrode, inhibiting the growth of sodium dendrites, and improving the cycle life and Coulomb efficiency; the porosity and dispersibility of the nanoarray structure can inhibit the growth of sodium dendrites and reduce the short circuit and safety risks caused by sodium dendrites; the nanoarray structure as a skeleton can provide good mechanical strength and chemical stability, which helps to form a stable solid electrolyte interface (SEI). A stable SEI can prevent the active substances in the electrolyte from interacting with sodium metal, reducing the rupture of the SEI layer and the loss of battery capacity;
[0020] 6. The electrode design method of the flexible nanoarray structure of the present invention avoids the use of adhesives and conductive additives, reduces the internal resistance of the electrode material, is conducive to maintaining the excellent rate and cycle performance of the electrode material, effectively alleviates volume expansion and inhibits sodium dendrites, and can effectively improve the utilization rate of active materials and battery cycle performance. DETAILED DESCRIPTION
[0021] The technical solution of the present invention will be clearly and completely described below in conjunction with embodiments.
[0022] All raw materials used in the examples are commercially available unless otherwise specified. The conductive carbon cloth used is HCP331N produced by Shenzhen Kejing Zhida Technology Co., Ltd., and has a thickness of 0.3 mm.
[0023] Example 1
[0024] The method for preparing the flexible sodium-sulfur battery comprises the following steps:
[0025] (1) A 9 cm × 10 cm conductive carbon cloth was ultrasonically cleaned with 3 M hydrochloric acid, acetone, anhydrous ethanol and deionized water in sequence to remove pollutants such as organic matter and oxide layer on the surface. The cleaned conductive carbon cloth was placed in an oven and dried at 60 ° C for 5 h. The cleaned and dried conductive carbon cloth was heated at 500 ° C for 6 h in a muffle furnace for activation treatment.
[0026] (2) Preparation of NiCoMoS@CC positive electrode: 2mmolNi(NO3)2·6H2O, 2mmolCo(NO3)2·6H2O, 2mmolNa2MoO4, 600mgurea and 150mgNH4F were dissolved in deionized water, magnetically stirred until uniformly dissolved, and then vacuum and ultrasonically treated for 30min to obtain a mixed solution. In the mixed solution, the concentrations of Ni(NO3)2·6H2O, Co(NO3)2·6H2O and Na2MoO4 were all 0.2M, the concentration of urea was 6g / L, and the concentration of NH4F was 1.5g / L. The activated conductive carbon cloth was immersed in the mixed solution and sealed. The NiCoMoLDHs@CC skeleton was obtained by heating the NiCoMoLDHs@CC skeleton in a polytetrafluoroethylene-lined stainless steel autoclave (specification 200 mL) at 150 ° C for 6 h for hydrothermal reaction, and then naturally cooled to room temperature to obtain a carbon cloth electrode loaded with a precursor, and the carbon cloth electrode loaded with a precursor was ultrasonically cleaned 3 times with deionized water, and then dried in an oven at 60 ° C for 5 h to obtain a NiCoMoLDHs@CC skeleton. The NiCoMoLDHs@CC skeleton was placed in a polytetrafluoroethylene-lined stainless steel autoclave in 100 mL of a 0.2 M Na2S·9H2O aqueous solution and heated at 130 ° C for 10 h for hydrothermal vulcanization, and then washed with deionized water and ethanol for 3 times respectively, and dried in a vacuum oven at 80 ° C for 5 h;
[0027] (3) Preparation of NiCoMoLDHs@CC-Na composite negative electrode: The NiCoMoLDHs@CC skeleton was brought into contact with molten metallic sodium heated at 150°C in a drying room, and the NiCoMoLDHs@CC-Na composite negative electrode was obtained by spontaneous adsorption of molten sodium.
[0028] Example 2
[0029] The method for preparing the flexible sodium-sulfur battery comprises the following steps:
[0030] (1) A 9 cm × 10 cm conductive carbon cloth was ultrasonically cleaned with 3 M hydrochloric acid, acetone, anhydrous ethanol and deionized water in sequence to remove pollutants such as organic matter and oxide layer on the surface. The cleaned conductive carbon cloth was placed in an oven and dried at 60 ° C for 5 h. The cleaned and dried conductive carbon cloth was heated at 600 ° C for 5 h in a muffle furnace for activation treatment.
[0031] (2) Preparation of NiCoMoS@CC positive electrode: 2mmolNi(NO3)2·6H2O, 1mmolCo(NO3)2·6H2O, 2mmolNa2MoO4, 300mgurea and 100mgNH4F were dissolved in deionized water, magnetically stirred until uniformly dissolved, and then vacuum and ultrasonically treated for 40min to obtain a mixed solution. In the mixed solution, the concentrations of Ni(NO3)2·6H2O and Na2MoO4 were 0.2M, the concentration of Co(NO3)2·6H2O was 0.1M, the concentration of urea was 3g / L, and the concentration of NH4F was 1g / L. The activated conductive carbon cloth was immersed in the mixed solution and heated in a dense The NiCoMoLDHs@CC skeleton was obtained by heating the NiCoMoLDHs@CC skeleton in a sealed polytetrafluoroethylene-lined stainless steel autoclave (specification 200 mL) at 140 °C for 10 h for hydrothermal reaction, and then naturally cooled to room temperature to obtain a carbon cloth electrode loaded with a precursor, and the carbon cloth electrode loaded with a precursor was ultrasonically cleaned 3 times with deionized water, and then dried in an oven at 60 °C for 5 h to obtain a NiCoMoLDHs@CC skeleton. The NiCoMoLDHs@CC skeleton was placed in a polytetrafluoroethylene-lined stainless steel autoclave in 100 mL of a 0.1 M Na2S·9H2O aqueous solution and heated at 120 °C for 12 h for hydrothermal vulcanization, and then washed with deionized water and ethanol for 3 times respectively, and dried in a vacuum oven at 80 °C for 5 h;
[0032] (3) Preparation of NiCoMoLDHs@CC-Na composite negative electrode: The NiCoMoLDHs@CC skeleton was brought into contact with molten metallic sodium heated at 150°C in a drying room, and the NiCoMoLDHs@CC-Na composite negative electrode was obtained by spontaneous adsorption of molten sodium.
[0033] Example 3
[0034] The method for preparing the flexible sodium-sulfur battery comprises the following steps:
[0035] (1) A 9 cm × 10 cm conductive carbon cloth was ultrasonically cleaned with 3 M hydrochloric acid, acetone, anhydrous ethanol and deionized water in sequence to remove pollutants such as organic matter and oxide layer on the surface. The cleaned conductive carbon cloth was placed in an oven and dried at 60 ° C for 5 h. The cleaned and dried conductive carbon cloth was heated at 400 ° C for 8 h in a muffle furnace for activation treatment.
[0036] (2) Preparation of NiCoMoS@CC positive electrode: 1mmolNi(NO3)2·6H2O, 1mmolCo(NO3)2·6H2O, 1mmolNa2MoO4, 400mgurea and 80mgNH4F were dissolved in deionized water, magnetically stirred until uniformly dissolved, and then vacuum and ultrasonically treated for 60min to obtain a mixed solution. In the mixed solution, the concentrations of Ni(NO3)2·6H2O, Co(NO3)2·6H2O and Na2MoO4 were all 0.1M, the concentration of urea was 4g / L, and the concentration of NH4F was 0.8g / L. The activated conductive carbon cloth was immersed in the mixed solution and sealed. The NiCoMoLDHs@CC skeleton was obtained by heating the NiCoMoLDHs@CC skeleton in a polytetrafluoroethylene-lined stainless steel autoclave (specification 200 mL) at 180 ° C for 4 h for hydrothermal reaction, and then naturally cooled to room temperature to obtain a carbon cloth electrode loaded with a precursor, and the carbon cloth electrode loaded with a precursor was ultrasonically cleaned 3 times with deionized water, and then dried in an oven at 60 ° C for 5 h to obtain a NiCoMoLDHs@CC skeleton. The NiCoMoLDHs@CC skeleton was placed in a polytetrafluoroethylene-lined stainless steel autoclave in 100 mL of a 0.1 M Na2S·9H2O aqueous solution and heated at 130 ° C for 8 h for hydrothermal vulcanization, and then washed with deionized water and ethanol for 3 times respectively, and dried in a vacuum oven at 80 ° C for 5 h;
[0037] (3) Preparation of NiCoMoLDHs@CC-Na composite negative electrode: The NiCoMoLDHs@CC skeleton was brought into contact with molten metallic sodium heated at 150°C in a drying room, and the NiCoMoLDHs@CC-Na composite negative electrode was obtained by spontaneous adsorption of molten sodium.
[0038] Example 4
[0039] The method for preparing the flexible sodium-sulfur battery comprises the following steps:
[0040] (1) A 9 cm × 10 cm conductive carbon cloth was ultrasonically cleaned with 3 M hydrochloric acid, acetone, anhydrous ethanol and deionized water in sequence to remove pollutants such as organic matter and oxide layer on the surface. The cleaned conductive carbon cloth was placed in an oven and dried at 60 ° C for 5 h. The cleaned and dried conductive carbon cloth was heated at 700 ° C for 4 h in a muffle furnace for activation treatment.
[0041] (2) Preparation of NiCoMoS@CC positive electrode: 1mmolNi(NO3)2·6H2O, 2mmolCo(NO3)2·6H2O, 2mmolNa2MoO4, 500mgurea and 120mgNH4F were dissolved in deionized water, magnetically stirred until uniformly dissolved, and then vacuum and ultrasonically treated for 60min to obtain a mixed solution. In the mixed solution, the concentration of Ni(NO3)2·6H2O was 0.1M, the concentrations of Co(NO3)2·6H2O and Na2MoO4 were both 0.2M, the concentration of urea was 5g / L, and the concentration of NH4F was 1.2g / L. The activated conductive carbon cloth was immersed in the mixed solution. The reaction was carried out by heating at 160°C for 5 h in a sealed polytetrafluoroethylene-lined stainless steel autoclave (200 mL), and then naturally cooled to room temperature to obtain a carbon cloth electrode loaded with a precursor. The carbon cloth electrode loaded with a precursor was ultrasonically cleaned 3 times with deionized water, and then dried in an oven at 60°C for 5 h to obtain a NiCoMoLDHs@CC skeleton. The NiCoMoLDHs@CC skeleton was placed in a polytetrafluoroethylene-lined stainless steel autoclave in 100 mL of a 0.1 M Na2S·9H2O aqueous solution and heated at 120°C for 10 h for hydrothermal vulcanization. Then, it was washed 3 times with deionized water and ethanol, respectively, and dried in a vacuum oven at 80°C for 5 h.
[0042] (3) Preparation of NiCoMoLDHs@CC-Na composite negative electrode: The NiCoMoLDHs@CC skeleton was brought into contact with molten metallic sodium heated at 150°C in a drying room, and the NiCoMoLDHs@CC-Na composite negative electrode was obtained by spontaneous adsorption of molten sodium.
[0043] Comparative Example 1
[0044] The difference between this comparative example 1 and example 1 is that in step (2), an equimolar amount of Mn(NO3)2•4H2O is used to replace Na2MoO4 to obtain a NiCoMnS@CC positive electrode and a NiCoMnLDHs@CC-Na composite negative electrode.
[0045] Comparative Example 2
[0046] The difference between this comparative example 2 and example 1 is that in step (2), an equimolar amount of Fe(NO3)3•9H2O is used to replace Na2MoO4 to obtain a NiCoFeS@CC positive electrode and a NiCoFeLDHs@CC-Na composite negative electrode.
[0047] Comparative Example 3
[0048] The only difference between Comparative Example 3 and Example 2 is that the conductive carbon cloth is replaced by nickel foam of the same size.
[0049] Comparative Example 4
[0050] The only difference between Comparative Example 4 and Example 3 is that NH4F is not added in step (2).
[0051] Comparative Example 5
[0052] The difference between this comparative example 5 and example 4 is that in step (3), the NiCoMoLDHs@CC skeleton is not melt-compounded with metallic sodium, but is electrochemically deposited by sodium ions, specifically, sodium metal is used as the positive electrode and the NiCoMoLDHs@CC skeleton is used as the negative electrode, and is prepared by electrodepositing sodium ions onto the NiCoMoLDHs@CC skeleton.
[0053] The positive and negative electrode materials prepared in Examples 1-4 and Comparative Examples 1-5 are assembled into full batteries. The specific battery assembly process is as follows:
[0054] The NiCoMoS@CC positive electrode material (NiCoMnS@CC positive electrode in comparative example 1, NiCoFeS@CC positive electrode in comparative example 2) is used as the positive electrode, the NiCoMoLDHs@CC-Na composite negative electrode material (NiCoMnLDHs@CC-Na composite negative electrode in comparative example 1, NiCoFeLDHs@CC-Na composite negative electrode in comparative example 2) is used as the negative electrode, 2 mol / L NaTFSI is used as the electrolyte dissolved in DME (ethylene glycol dimethyl ether) ether solvent, and a ceramic diaphragm is used to assemble the sodium-sulfur battery. The test results of the discharge specific capacity and capacity retention rate of the obtained sodium-sulfur battery after 100 cycles of charge and discharge at 0.1C are shown in Table 1.
[0055] Table 1 Test results of battery discharge specific capacity and capacity retention rate of Examples 1-4 and Comparative Examples 1-5
[0056]
[0057] It can be seen from Table 1 that the full battery assembled with the positive and negative electrode materials of Comparative Examples 1 and 2 has a lower discharge capacity and capacity retention rate after 100 cycles than the full battery assembled with the positive and negative electrode materials of Example 1. This is because the stability of iron and manganese during the charge and discharge process of the sodium-sulfur battery is slightly worse. Iron dissolves and migrates in sodium-sulfur batteries, affecting the cycle stability of the battery. Manganese is prone to redox reactions during the charge and discharge process, resulting in structural instability and capacity decay, especially Mn 3+ / Mn 2+The transition between them may trigger the Jahn-Teller effect, causing manganese dissolution and affecting the performance of sodium-sulfur batteries. Compared with NiCoFeS and NiCoMnS, NiCoMoS has a highly efficient electrocatalytic effect, which can promote the conversion of polysulfides into Na2S, effectively avoid the dissolution and shuttling of polysulfides, thereby improving the cycle performance and high-rate performance of sodium-sulfur batteries. NiCoMoS also has excellent chemical adsorption effect and strong adsorption capacity for polysulfides, which helps to prevent the dissolution and shuttling of polysulfides during battery operation, thereby reducing the loss of battery capacity and improving the cycle stability of the battery. NiCoMoS has enhanced electronic conductivity, thereby improving the discharge capacity and cycle stability of the battery. In addition, NiCoMoS has good structural stability and high capacity retention rate after multiple charge and discharge cycles.
[0058] The full battery assembled with the positive and negative electrode materials of Comparative Example 3 has lower discharge capacity and capacity retention rate after 100 cycles than that of Example 2. This is because although nickel foam has a high surface area and good chemical stability, its mechanical stability is relatively poor. As the number of charge and discharge cycles increases, the active material may fall off, affecting the cycle stability of the sodium-sulfur battery. Carbon cloth has high conductivity and good chemical stability. Carbon materials are not easy to react chemically with electrolytes, etc., and have good flexibility.
[0059] The full battery assembled with the positive and negative electrode materials of Comparative Example 4 has lower discharge specific capacity and capacity retention rate after 100 cycles than that of Example 3. This is because the addition of NH4F helps to improve the conductivity of the electrode material and can also control the morphology of the transition metal sulfide, which helps to increase the effective area of the electrode reaction, thereby improving the energy density, and can also improve its chemical and electrochemical stability, thereby improving the cycle stability of the sodium-sulfur battery.
[0060] The full battery assembled with the positive and negative electrode materials of Comparative Example 5 has lower discharge specific capacity and capacity retention rate after 100 cycles than Example 4. Although electrochemical deposition can accurately control the thickness, composition and microstructure of the deposit by adjusting parameters such as current density, voltage, time and electrolyte composition. However, the thickness of the metallic sodium deposited on NiCoMoLDHs@CC is inconsistent, and problems such as coarse grains and high porosity may occur, affecting the stability and durability of the sodium-sulfur battery. Side reactions are prone to occur during the electrochemical deposition process, resulting in reduced deposition efficiency. In addition, in order to drive the deposition reaction, it is often necessary to overcome a large overpotential, which affects the energy utilization efficiency. The molten metallic sodium is compounded with the NiCoMoLDHs@CC skeleton, and the composited NiCoMoLDHs@CC-Na has flexibility. In addition, the carbon cloth has a three-dimensional structure, which can effectively reduce the local current density, induce uniform deposition, and thus inhibit the growth of sodium dendrites. The mechanical properties and stability of the negative electrode material can also be enhanced by compounding the molten metallic sodium with the carbon cloth, and it has excellent electrochemical cycle stability.
Claims
1. A method for preparing a flexible sodium-sulfur battery, characterized in that: The steps include: (1) ultrasonically cleaning the conductive carbon cloth using hydrochloric acid, acetone, anhydrous ethanol and deionized water in sequence, drying the cleaned conductive carbon cloth, and then heating the cleaned and dried conductive carbon cloth for activation treatment; (2) Preparation of NiCoMoS@CC positive electrode: Ni(NO3)2·6H2O, Co(NO3)2·6H2O, Na2MoO4, urea and NH4F were dissolved in deionized water, stirred, and vacuum and ultrasonically treated to obtain a mixed solution. The activated carbon cloth was immersed in the mixed solution, sealed and heated for hydrothermal reaction, and then naturally cooled to room temperature to obtain a carbon cloth electrode loaded with the precursor. The carbon cloth electrode loaded with the precursor was ultrasonically cleaned with deionized water and then dried to obtain a NiCoMoLDHs@CC skeleton. The NiCoMoLDHs@CC skeleton was heated in a Na2S·9H2O aqueous solution for hydrothermal sulfurization, then washed with deionized water and ethanol, and vacuum dried. (3) Preparation of NiCoMoLDHs@CC-Na composite anode: The NiCoMoLDHs@CC skeleton was brought into contact with heated molten metallic sodium in a drying room, and the NiCoMoLDHs@CC-Na composite anode was obtained by spontaneous adsorption of molten sodium.
2. The method for preparing a flexible sodium-sulfur battery according to claim 1, characterized in that: In step (1), the cleaned and dried conductive carbon cloth is activated by heating it at 400-700° C. for 4-8 hours in a muffle furnace in an argon atmosphere.
3. The method for preparing a flexible sodium-sulfur battery according to claim 1, characterized in that: In step (2), in the mixed solution, the concentrations of Ni(NO3)2·6H2O, Co(NO3)2·6H2O, and Na2MoO4 are all 0.01-0.02M.
4. The method for preparing a flexible sodium-sulfur battery according to claim 1, characterized in that: In step (2), in the mixed solution, the mass volume concentration of urea is 3-6 g / L, the mass volume concentration of NH4F is 0.8-1.5 g / L, and the vacuum and ultrasonic treatment time is 30-60 min.
5. The method for preparing a flexible sodium-sulfur battery according to claim 1, characterized in that: In step (2), the hydrothermal reaction is carried out at 140-180° C. for 4-10 hours.
6. The method for preparing a flexible sodium-sulfur battery according to claim 1, characterized in that: In step (2) of hydrothermal vulcanization, the concentration of Na2S·9H2O in the Na2S·9H2O aqueous solution is 0.1-0.2M, the hydrothermal vulcanization temperature is 120-130°C, and the hydrothermal vulcanization time is 8-12h.
7. A flexible sodium-sulfur battery prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Preparation method and application of porous carbon fiber / tungsten oxide self-supporting lithium-sulfur battery positive electrode material
CN113972375A
Method for preparing lithium and sodium ion battery electrode material and modified battery diaphragm
CN114843463A